2000
DOI: 10.1083/jcb.148.4.769
|View full text |Cite
|
Sign up to set email alerts
|

A Transmembrane Segment Determines the Steady-State Localization of an Ion-Transporting Adenosine Triphosphatase

Abstract: The H,K-adenosine triphosphatase (ATPase) of gastric parietal cells is targeted to a regulated membrane compartment that fuses with the apical plasma membrane in response to secretagogue stimulation. Previous work has demonstrated that the α subunit of the H,K-ATPase encodes localization information responsible for this pump's apical distribution, whereas the β subunit carries the signal responsible for the cessation of acid secretion through the retrieval of the pump from the surface to the regulated intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
73
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 47 publications
(59 reference statements)
0
73
0
Order By: Relevance
“…Lipid rafts are liquid-ordered membrane microdomains rich in cholesterol and glycosphingolipids that serve as platforms or converging centers for decoding apical sorting information (1, 11). Other transmembrane domains direct apical destination without raft association (5). Apical sorting information also is found in the cytosolic domain of polytopic proteins (7,8,12), suggesting decoding mechanisms similar to those of basolateral membrane proteins.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Lipid rafts are liquid-ordered membrane microdomains rich in cholesterol and glycosphingolipids that serve as platforms or converging centers for decoding apical sorting information (1, 11). Other transmembrane domains direct apical destination without raft association (5). Apical sorting information also is found in the cytosolic domain of polytopic proteins (7,8,12), suggesting decoding mechanisms similar to those of basolateral membrane proteins.…”
mentioning
confidence: 84%
“…It is difficult to identify sorting information in multispan membrane proteins, unless a set of isoforms or highly homologous proteins with opposite polarity allow screening by comparison, deletions, and͞or mixing domains in hybrid proteins (5,8). The sorting behavior of other isoforms of hSlo have not been explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have identified dominant sorting signals in the nonglycosylated catalytic ␣-subunit in Na ϩ ,K ϩ -ATPase and H ϩ ,K ϩ -ATPase (33,34) that are responsible for the basolateral or apical localization, respectively, of the heterodimeric pump. The basolateral localization of Na ϩ ,K ϩ -ATPase is additionally stabilized by interactions of the ␣-subunit with ankyrin at the lateral membrane (35) and by interactions between neighboring ␤-subunits (36).…”
Section: Discussionmentioning
confidence: 99%
“…PDZ domains are modules for protein-protein interaction and are involved in sorting and͞or the stability of asymmetrically distributed proteins (30,31). The findings that NaPi-Cap1 and NHERF1 are expressed in the renal proximal BBM and interact with the C-terminal tail of NaPi IIa in a PDZ-motif-dependent manner, together with the observation that this terminal PDZmotif contains information for apical expression, prompted us to analyze whether such interactions are involved in apical expression of NaPi IIa.…”
mentioning
confidence: 99%